2023
DOI: 10.3390/ijerph20065035
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Health Workforce Policy during a Major Global Health Crisis: A Critical Conceptual Debate and International Empirical Investigation

Abstract: Background: The health workforce is central to healthcare systems and population health, but marginal in comparative health policy. This study aims to highlight the crucial relevance of the health workforce and contribute comparative evidence to help improve the protection of healthcare workers and prevention of inequalities during a major public health crisis. Methods: Our integrated governance framework considers system, sector, organizational and socio-cultural dimensions of health workforce policy. The COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…However, we are also decreasing in terms of workforce number as a specialty and because of the Pandemic, as doctors in general. [8][9][10] We need rapid identification or assessment of conditions in order not to delay treatment. Much rheumatologic research has been shown to be promising in radiographs, 11 magnetic resonance imaging, 12 and even musculoskeletal ultrasound.…”
Section: A S a Clini Cianmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we are also decreasing in terms of workforce number as a specialty and because of the Pandemic, as doctors in general. [8][9][10] We need rapid identification or assessment of conditions in order not to delay treatment. Much rheumatologic research has been shown to be promising in radiographs, 11 magnetic resonance imaging, 12 and even musculoskeletal ultrasound.…”
Section: A S a Clini Cianmentioning
confidence: 99%
“…As a clinical rheumatologist, I welcome the opportunity for assistance in clinic or hospital tasks. However, we are also decreasing in terms of workforce number as a specialty and because of the Pandemic, as doctors in general 8–10 . We need rapid identification or assessment of conditions in order not to delay treatment.…”
Section: As a Clinicianmentioning
confidence: 99%
“…Patient outcomes are worse, care is less efficient, working conditions decline, and staff morale is affected. 17,18 The World Health Organization has championed guidance around fair migration, and has noted the importance of higher-income settings producing, mobilising, and recruiting their own HCWF as opposed to recruiting internationally, especially from countries with low HCWF density. 19 The challenges that we have highlighted here cannot be overcome by the Ministry of Health alone.…”
Section: Introductionmentioning
confidence: 99%
“…Australia also shares a health workforce market with New Zealand (with many shared regulatory and quasi-regulatory aspects). This remuneration and landscape of worker conditions is complex and can be challenging to assess within the country, let alone in comparison to other countries (5, 6). Differences in workforce costs are important in assessing cost variance between jurisdictions and countries, in health policy decisions and in understanding the impact of labour costs on economic evaluation (7).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of microcosting a complex health service, diagnostic genomic testing for rare diseases and trying to understand the uncertainty of labour cost for this health service by jurisdiction (10), we identified a gap in available tools and resources for estimating public health workforce costs, specifically for genomics (pathology) workforce. A standardised Australian labour costing tool could be used to support comparative policy research within Australia (6) or for use in comparative health systems research with other countries (5). The application in this particular use case was to undertake a deterministic sensitivity analysis of clinical genomic testing by varying labour prices based on the estimated costs in Australian states with public clinical genomic testing services (10, 11).…”
Section: Introductionmentioning
confidence: 99%